2014
DOI: 10.1371/journal.pone.0084889
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Infiltrate the Pancreas via the MCP-1/CCR2 Pathway and Differentiate into Stellate Cells

Abstract: Recent studies have shown that monocytes possess pluripotent plasticity. We previously reported that monocytes could differentiate into hepatic stellate cells. Although stellate cells are also present in the pancreas, their origin remains unclear. An accumulation of enhanced green fluorescent protein (EGFP)+CD45– cells was observed in the pancreases and livers of chimeric mice, which were transplanted with a single hematopoietic stem cell isolated from EGFP-transgenic mice and treated with carbon tetrachloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Macrophage-produced growth factors and cytokines regulated SMAD7 expression in β-cells and subsequently influenced proliferation [53,68,69]. …”
Section: Introductionmentioning
confidence: 99%
“…Macrophage-produced growth factors and cytokines regulated SMAD7 expression in β-cells and subsequently influenced proliferation [53,68,69]. …”
Section: Introductionmentioning
confidence: 99%
“…Mouse models of type 2 diabetes showed changes of islet macrophages to a proinflammatory profile (M1; Cucak et al, 2014 ; Westwell-Roper et al, 2014 ). Concerning the exocrine pancreas, macrophages were examined mostly in pathological situations (inflammation after ductal ligation, carbon tetrachloride–induced pancreatitis, and experimental pancreatic cancer) and limited studies under steady state ( Yin et al, 2011 ; Ino et al, 2014 ; Xiao et al, 2014 ).…”
mentioning
confidence: 99%
“…Although the origin of PSCs is not clear, it was demonstrated that a proportion of PSCs originate from bone marrow and replenish PSCs in the pancreas (38). In addition, Ino et al (39) showed that chemokine receptor type 2 (CCR2 + ) monocytes migrate from the bone marrow and transform into PSCs through the monocyte chemoattractant protein-1 (MCP-1)/CCR2 pathway. The monocyte lineage origin of PSC is also supported by the expression of monocyte specific marker α-naphthyl butyrate esterase (ANBE) (40).…”
Section: Pscs In the Healthy Pancreasmentioning
confidence: 99%